2020
DOI: 10.1371/journal.pone.0226816
|View full text |Cite
|
Sign up to set email alerts
|

Functional interactions in patients with hemianopia: A graph theory-based connectivity study of resting fMRI signal

Abstract: The assessment of task-independent functional connectivity (FC) after a lesion causing hemianopia remains an uncovered topic and represents a crucial point to better understand the neural basis of blindsight (i.e. unconscious visually triggered behavior) and visual awareness. In this light, we evaluated functional connectivity (FC) in 10 hemianopic patients and 10 healthy controls in a resting state paradigm. The main aim of this study is twofold: first of all we focused on the description and assessment of de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 105 publications
0
8
0
Order By: Relevance
“…Previous studies found that PD patients with freezing of gait showed reduced network connectivity in the visual network (VN; Rogge et al, 2018 ; Ruan et al, 2020 ). The VN is composed of bilateral striate and extrastriata visual Areas ( Pedersini et al, 2020 ). Visual proprioceptive conflict may affect gait and balance, and visual cues can improve balance and prevent falls in patients with PD ( Assländer et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies found that PD patients with freezing of gait showed reduced network connectivity in the visual network (VN; Rogge et al, 2018 ; Ruan et al, 2020 ). The VN is composed of bilateral striate and extrastriata visual Areas ( Pedersini et al, 2020 ). Visual proprioceptive conflict may affect gait and balance, and visual cues can improve balance and prevent falls in patients with PD ( Assländer et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our results indicated association between enhanced VN function and improved BBS scores. The VN was composed by bilateral striate and extrastriate visual areas [25]. Visual-proprioceptive sensory con ict could in uence gait and balance [26].…”
Section: Discussionmentioning
confidence: 99%
“…We also observed change of DMN was related to improvement in UPDRS and UPDRS-III. The DMN included the hippocampus, parahippocampal, fusiform and angular gyrus, the precuneus and the middle temporal gyrus [25]. Precuneus is one of the functional hub regions of DMN, and its interactions with sensorimotor network were positively associated with motor performances [29].…”
Section: Discussionmentioning
confidence: 99%
“…The current study investigated the alterations of functional organization for ON patients using a recently developed FCD method. FCD, a reliable rs-fMRI analytical method has been widely used in the study of various ophthalmic and neurological diseases ( Wang et al, 2014 ; Qin et al, 2015 ; Zhai et al, 2016 ; Hu et al, 2017 ; Chen et al, 2019 ; Li et al, 2019 ; Dai et al, 2020 ; Pedersini et al, 2020 ; Table 4 ). In addition to impaired visual function, the ON group showed significantly reduced longFCD values compared with HCs in the left IFGtriang, right PCUN, right ACG/DCG, and left DCG/SMA ( Figure 3 ).…”
Section: Discussionmentioning
confidence: 99%